High‐dose Methotrexate plus temozolomide with or without rituximab in patients with untreated primary central nervous system lymphoma: A retrospective study from China. (1st March 2019) - Chen, Cui; Sun, Peng; Cui, Juan; Yan, Shumei; Chen, Hao; Xia, Yi; Bi, Xiwen; Liu, Panpan; Wang, Yu; Yang, Hang; Nie, Man; Zhang, Xue‐Wen; et al.
Abstract: The purpose of this retrospective study was to compare the efficacy and toxicity of high‐dose methotrexate plus temozolomide (MT regimen) and rituximab plus MT (RMT regimen) in patients with untreated primary central nervous system lymphoma (PCNSL). A total of 62 patients with untreated PCNSL were enrolled between January 2005 and December 2015, with the median age of 53.5 years (range 29‐77).In this study, 32 patients received RMT as induction therapy, and 30 received MT. Objective responses were noted in 93.7% of the patients in the RMT group and in 69.0% of the patients in the MT group ( P  = 0.018), while complete responses were noted in 53.2% of the patients in the RMT group and 27.6% of the patients in the MT group ( P  < 0.001). The 2‐ and 5‐year PFS rates were 81.3% and 53.3%, respectively, for the RMT group and 46.5% and 29.1%, respectively, for the MT group ( P  = 0.019). The 2‐ and 5‐year overall survival (OS) rates were 82.3% and 82.3%, respectively, for the RMT group and 65.7% and 50.0%, respectively, for the MT group ( P  = 0.015). Multivariate analyses showed that therapeutic regimen (RMT vs MT) was an independent prognostic factor for PFS and OS. Our encouraging results suggest that the RMT regimen may be a feasible and safe therapeutic approach for first‐line treatment of PCNSL. Abstract : The purpose of this study was to compare the efficacy and toxicity of high‐dose methotrexate plus temozolomide (MT regimen) and of rituximab plus MT (RMT regimen) in untreated PCNSL. Our encouraging results suggest that the RMT regimen might be a feasible and safe therapeutic approach in the first‐line treatment of PCNSL.